2003
DOI: 10.3758/bf03194402
|View full text |Cite
|
Sign up to set email alerts
|

“If I didn’t write it, why would I remember it?” Effects of encoding, attention, and practice on accurate and false memory

Abstract: In two experiments involving recall and recognition, we manipulated encoding strategies,attention, and practice in the Deese, Roediger, and McDermott false memory procedure. During the study of auditory word lists, participants listened to the words, wrote the words, wrote the second letter of the words, or counted backward by threes and wrote numbers in time with the words. The results from both experiments showed that, relative to the full-attention hear word condition, the divided-attention write number con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 51 publications
4
33
0
Order By: Relevance
“…However, these studies also found a similar decrease in false recognition under divided attention whereas the current results did not reveal any effect of divided attention for false recognition. This latter finding is more consistent with Seamon et al's (2003) study that did not find any effect of divided attention on false recognition in adults. It is possible that the secondary task used may account for the differences in findings across studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, these studies also found a similar decrease in false recognition under divided attention whereas the current results did not reveal any effect of divided attention for false recognition. This latter finding is more consistent with Seamon et al's (2003) study that did not find any effect of divided attention on false recognition in adults. It is possible that the secondary task used may account for the differences in findings across studies.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, when introducing an additional memory load at encoding rather than using a divided attention paradigm, false recognition is reduced (but only in a between-participants condition not in a within-participant design) (Seamon, et al, 1998). It has also been shown that divided attention at encoding impairs true recognition but not false recognition (Seamon et al, 2003).…”
Section: Divided Attentionmentioning
confidence: 99%
“…For example, Jennings and Jacoby (1993) found dividing attention at study to increase false fame errors. However, to our knowledge, only a few studies have examined the impact of dividing attention on the occurrence of false memories in the DRM paradigm (Payne, Lampinen, & Cordero, 1996, cited in Roediger et al, 1998Perez-Mata et al, 2002;Seamon et al, 1998Seamon et al, , 2003. These studies only manipulated divided attention at study and their results were mixed.…”
Section: Methodsmentioning
confidence: 99%
“…In a later study, Seamon et al (2003) used a range of orienting tasks to manipulate the level of attention allocated to DRM lists. Two tasks (writing the words or writing the second letter of each word as it was presented) were designed to focus attention on the DRM lists, whereas a third task (counting backward in threes and writing the numbers in pace with the presentation of the DRM stimuli) was designed to divide attention.…”
mentioning
confidence: 99%